Penggunaan Media Pembelajaran Quizizz untuk Meningkatkan Hasil Belajar Siswa Sekolah Dasar - Arrahim Arrahim; Hana Yulianti; Rini Endah Sugiharti (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2022)
This research is motivated by there are still children who have not reached the Minimum Completion Criteria. The low learning outcomes of students are due to lack of understanding when doing questions and lack of use of learning media.  Therefore, quizizz learning media is used as a solution to overcome these problems, because quizizz learning   media can make students more active in learning, Eliminates boredom in students, increases student motivation in learning so that it has an impact on   optimal student learning outcomes. The research method used is Systematic Literature Review (SLR). By studying or studying and analyzing how the use of Quizizz Learning Media describes the Learning Outcomes of Elementary School Students. The analysis sample is 15 published scientific journals published in the range of 2020-2022. Those that have been excluded from several scientific articles use the keywords "Quizizz Learning Media", "Learning Outcomes", "Elementary School Students" and "Quizizz Learning Media Against Elementary School Student Learning Outcomes". Based on the results of the analysis of scientific articles that have been collected, the application of quiziz learning media helps students in understanding the learning material, helps students to be active in learning, student motivation in learning, relieving student boredom, and providing a pleasant learning atmosphere so that it has an impact on improving student learning outcomes.